Neuromelioidosis: A Single-Center Experience with Emphasis on Imaging - Mannam, Pavithra; Arvind, Vanjare H.; Koshy, Maria; Varghese, George M.; Alexander, Mathew; Elizabeth, Sunithi M. (Indian Journal of Radiology and Imaging, 2021)
Introduction Infection with Burkholderia pseudomallei, a gram-negative bacterium found in soil and surface water, is termed melioidosis and is commonly reported to occur in Southeast Asia and Northern Australia, where it is endemic. It is being increasingly reported in India, and transmission occurs through inhalation, inoculation, and ingestion. The neuroparenchyma, the adjacent soft tissue, and bone are known to be affected in both the acute and chronic disease forms. Involvement of these structures is rare but causes significant mortality and morbidity.Material and Methods Eighteen culture-proven cases of neuromelioidosis were identified between January 2008 and December 2019. The patients were retrospectively identified via search of the hospital’s electronic database.Results Cranial disease was in the form of parenchymal abscesses (n = 4), cerebritis/encephalitis (n = 5), and extradural (n = 4) and dural disease (n = 1). Acute myelitis (n = 1) and spondylodiscitis (n = 3) were seen in the spinal disease form. Neuroparenchymal involvement ranged from cerebritis/encephalitis to early and mature parenchymal abscesses. Extradural involvement was in the form of extradural abscesses and/or thick irregular enhancement in the extradural region. Early diagnosis and initiation of appropriate therapy had favorable outcomes in 15 out of 18 patients. Two patients with parenchymal abscesses and one with myelitis succumbed to the illness.Conclusion Neuromelioidosis is a rare manifestation of melioidosis with significant morbidity and mortality, necessitating a high index of clinical suspicion, especially if there has been travel to endemic regions. Imaging plays a key role in facilitating early diagnosis and initiation of therapy.
Keywords: brain abscess; Burkholderia pseudomallei; calvarial osteomyelitis; neuromelioidosis; scalp collection